Associations between life’s essential 8 and preserved ratio impaired spirometry - Yuxin Lai; Tianshu Yang; Xiaomei Zhang; Mengqian Li (Scientific Reports)
Abstract Preserved ratio impaired spirometry (PRISm) is a prevalent yet under-researched state of diminished lung function, which has been proposed as a pre-clinical abnormal spirometry associated with chronic obstructive pulmonary disease (COPD) or early-stage COPD. PRISm is closely associated with cardiovascular disease. Preventing and improving quality of life in PRISm subjects is important. We aimed to examined the relationship between American Heart Association’s Life’s Essential 8 (LE8) and PRISm. This cross-sectional study utilized data of 2,869 adults aged ≥ 20 years from the National Health and Nutrition Examination Survey (NHANES) in 2007–2012. Multivariable logistic regression models were employed to examine the association between LE8 score, health behavior score, health factor score, each component of LE8 score, and PRISm. Moreover, the study explored this correlation in greater depth using restricted cubic spline curves and subgroup analyses. Of the 2,869 participants, the mean age was 44.09 ± 0.44 years, and 316 (11.01%) were defined as having PRISm. In fully adjusted models, higher LE8 scores were associated with a reduced odds ratio for PRISm (OR = 0.97; 95% CI, 0.96–0.98). A linear relationship between the LE8 score and PRISm was observed. Similar patterns emerged for health behavior and health factor subscores, with a particularly stronger correlation between health factors and PRISm. In the subgroup analysis, the inverse association between LE8 and PRISm was significantly more pronounced among those with high income. A higher LE8 score was associated with a lower likelihood of developing PRISm. Promoting optimal adherence to the LE8 metrics may improve PRISm and offers a meaningful approach for its prevention and management.